Studies and Research on Obtaining Multifunctional Thin Films by Magnetron-Assisted PVD Process - Simona BOICIUC (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2021)
The paper aims to obtain thin films of nickel and zinc through the magnetron-assisted spraying process and their characterization from a structural point of view, of electrical, optical properties and corrosion resistance. It was found that as the intensity and discharge power increase, changes occur in the structure and properties of the deposited films.